Class, Power and the State in Capitalist Society
XV, 260 p.
Keywords: This collection of new essays re-examines and evaluates central themes in the work of Ralph Miliband, a leading contributor to Marxist political theory in twentieth century. It provides an essential reference point for research within the Marxist tradition, and a valuable resource for students on a range of courses in political and social theory.